Evaluating the Utilization of Antenatal Services and Birth Preparedness Among Pregnant Women in Remote Areas: A Cross-Sectional Study - Arifa Inayat, Bilal Masood, Juneda Sarfraz, Saira Hout, Bakhtawar Baloch, Uzma Asif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Antenatal care (ANC) and birth preparedness are essential components of safe motherhood, helping to reduce maternal and neonatal morbidity and mortality. However, in remote areas, the utilization of these services remains inadequate due to a range of sociodemographic and structural barriers. Objective: To evaluate the utilization of antenatal services and the level of birth preparedness among pregnant women residing in remote areas, and to identify key factors influencing maternal care-seeking behavior. Methods: A cross-sectional study was conducted at Sandeman Provincial Hospital, Quetta, from January 2022 to January 2023. Ninety pregnant women from remote rural regions in their third trimester were enrolled. Data were collected through a structured, interviewer-administered questionnaire assessing ANC visits, service components received, knowledge of danger signs, and birth preparedness indicators. Statistical analysis included descriptive measures and logistic regression to identify significant predictors. Results: Only 40% of women completed four or more ANC visits, and just 36.7% were adequately prepared for birth. Awareness of obstetric danger signs was low (28.9%). Maternal education and proximity to a healthcare facility were significantly associated with both ANC utilization (p = 0.034 and p = 0.011, respectively) and birth preparedness (p = 0.042). Most participants lacked financial planning and transport arrangements for delivery. Conclusion: ANC utilization and birth preparedness remain suboptimal in remote areas due to limited education, poor access, and lack of awareness. Strengthening community-based education, improving healthcare accessibility, and empowering women are critical to enhancing maternal outcomes in underserved populations. Keywords: Antenatal care, birth preparedness, maternal health, remote areas, pregnancy, healthcare access, Pakistan, obstetric danger signs, health education.